Associations between teachers’ professional competencies and the quality of interactions and relationships in preschool: findings from Austria - Embacher, Eva-Maria; Smidt, Wilfried (Frontiers in Psychology, 2023)
The professionalization of preschool teachers is considered an important factor for ensuring and improving the quality of interactions and relationships. Findings on associations between teachers’ professional competencies and the quality of interactions and relationships in preschools are not only inconsistent in general but also rare for early childhood education and care (ECEC) in Austria. Therefore, the aim of this study is to address this research gap by considering interaction quality at the child level (measured with the inCLASS) and preschool teachers’ perceptions of the teacher–child relationship (measured with the STRS). A sample of 287 children from 89 Austrian preschools was examined. After including control variables, the results of regression analyses revealed that preschool teachers’ beliefs on co-construction were negatively related to task orientation, whereas their beliefs on instruction were positively related to task orientation. Furthermore, preschool teachers’ work engagement was positively related to conflict interactions. Regarding teacher–child closeness, a positive association with preschool teachers’ work engagement was found. Results on teacher–child conflict showed a positive effect of preschool teachers’ beliefs on instruction and negative effects of teachers’ beliefs on co-construction and their self-efficacy. The findings are discussed in regard to the professionalization of preschool teachers.